Landslides Susceptibility Analysis Employing Analytical Hierarchy Process On An Amazonian Roadway In Ecuador [Análisis De Susceptibilidad A Deslizamientos Empleando El Proceso De Jerarquía Analítica En Una Carretera Amazónica Del Ecuador] - Cargua, Cristian J. (2024)
The Puyo-Tena roadway is prone to landslides due to the geodynamics, geomorphology, and geological materials of the area (unstable outcrops and strata). In recent years, this problem has persistently caused the road to be partially or completely disabled on numerous occasions. The objective of the research was to generate a cartographic model of landslides susceptibility based on variables such as slope, geological formations, land cover and land use, as well as distances to faults, road, and rivers. The degree of landslides incidence was estimated as the linear combination of the weighted variables using the analytic hierarchy process. The importance of this semi-quantitative method lies in its ability to break down a complex decision problem into a simpler and more coherent decision model. The resulting cartographic model was classified into five susceptibility categories: very low, low, moderate, high, and very high. The results showed that 17 km out of the 80 km of the Puyo-Tena roadway have a high probability of landslides, which is equivalent to 21.25% of the road. Furthermore, within this percentage, it was determined that there are fifteen regions with a high probability of landslides due to their location in areas with steep slopes, porous and permeable lithology, a large number of rivers, and agricultural soils. The area under the curve (AUC) of the receiver operating characteristic (ROC) was used for model verification. The verification results showed that the cartographic model for the study area has an accuracy value of 83.7%. The cartographic model of landslide susceptibility will enable relevant decisions to be made to mitigate potential hazards that may endanger transporters, material goods, and residents of the area.